How do bank-specific factors impact non-performing loans: Evidence from G20 countries - Mehmet Levent Erdas; Zeynep Ezanoglu (Journal of Central Banking Theory and Practice, 2022)
Banking is important for the stability and success of the economy. The success of the banking system on financial intermediation in developing countries is directly affected by non-performing loans (NPLs). Many factors can be treated as NPL determinants. Accordingly, the factors that explain NPLs contain very important information for banks. To this end, the study is an attempt to examine various banking factors that affect NPLs with respect to developing economies. In this study, the bank-specific and macroeconomic factors affecting the NPL rates were analysed through the dynamic panel data analysis. Analyses were made using described G20 countries between 1998 and 2017. The results indicate that the lagged value of NPLs, return on equity, credit growth and credit costs have a significant positive relationship with NPLs, while capital adequacy and GDP have a negative association with NPLs. The results confirm that if the bank-specific conditions change, the credit quality and bank management of banks are affected. It was concluded that the performance of banks is responsive to an effective loan monitoring policy. The findings of the study have implications for policymakers and regulators in the banking sector.
Keywords: G32; G01; G21; C23; F62; 330; Commercial Bank; Credit Risk; Dynamic Panel Data Analysis; Two-Step GMM; G20 Countries